FRI0037 Mer-mediated efferocytosis tempers arthritis by preventing neutrophils to go into secondary necrosis and spill their inflammatory content in the joint. (15th June 2017) - Waterborg, CEJ; Beermann, S; Bennink, MB; Koenders, MI; Lent, PLEM van; Hoogen, F van den; Kraan, PM van der; Loo, FAJ van de
Abstract : Background: Rheumatoid arthritis is characterized by an inflammatory response in synovial joints, showing a predominant influx of neutrophils. These cells are cytotoxic and contribute to matrix degradation. In addition, they are implicated as a source of citrullinated auto-antigens, leading to the production of anti-citrullinated protein antibodies. Neutrophils have a relative short life span and many of them undergo apoptosis. If they are not cleared, they undergo secondary necrosis and release their cell content. A key mediator in the resolution of inflammation and the uptake of apoptotic cells, or efferocytosis, is the receptor tyrosine kinase Mer. Objectives: To elucidate the local role of Mer during gonarthritis. Methods: Macrophages were transduced by adenoviruses encoding the Mer ligand Pros1 or Luciferase . One day after the collagen booster injection in mice, Mer-specific antibodies or IgG antibodies, or adenoviruses overexpressing Pros1 or Luciferase were injected intravenously. Mice were euthanized at day 30 or 36, respectively. The KRN serum transfer arthritis model was induced by two intraperitoneal injections of arthritic K/BxN serum in either Mer-deficient or wild-type (WT) mice, or in mice that overexpress Pros1 or Luciferase in their knee joints. Mice were euthanized at day 7 or day 14, respectively. From all mice, serum was taken for cytokine profiling and knee joints were isolated for either synovial gene expression or histology and immunohistochemistry. Results: Adenoviral overexpression of the Mer ligand Pros1 resulted in reduced production of pro-inflammatory cytokines and chemokines by macrophages, compared to Luciferase . In addition, local Pros1 overexpression resulted in reduced expression of pro-inflammatory and pro-destructive mediators by synovial cells of arthritic mice. Systemic and local Pros1 overexpression diminished joint pathology, reduced the number of cleaved Caspase 3-positive apoptotic cells and secondary necrotic neutrophils. Conversely, inhibiting Mer-mediated efferocytosis by either Mer-specific antibodies or Mertk gene ablation resulted in aggravation of arthritis compared to controls, as evidenced by increased inflammation and tissue destruction. Additionally, Mer-inhibited mice had increased numbers of apoptotic cells in their knee joints, and higher serum levels of IL-16C, a cytokine released by secondary necrotic neutrophils. Conclusions: Together, these results demonstrate that Mer locally plays a unique protective role in knee joint disease by enhancing resolution of arthritis. Our data suggest that promoting and/or restoring Mer-mediated uptake of apoptotic cells in the arthritic joint might be therapeutically beneficial. Disclosure of Interest: None declared